Association of Toll-Like Receptor 2 (TLR2) Expression in Placenta and Intrauterine Exposure to Hepatitis B Virus - Utami, Dian; Chalid, Maisuri T.; Masadah, Rina; Sjahril, Rizalinda; Bahagia Febriani, Andi Dwi (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Introduction. The placenta is a specialized organ that only performs during pregnancy and serves as an immunological barrier in preventing pathogens to reach the fetus. It has been known that toll-like receptors (TLRs) on the placenta respond to antigens, such as zymosan, lipopolysaccharide, and other viral infections. This study analyzes the distribution of TLR2 protein and hepatitis B DNA virus (HBV DNA) virus identification to gain an understanding of hepatitis B viral transmission from the mother to child. Methods. We performed enzyme-linked immunoadsorbent assay of HBeAg, HBsAg titer, Anti-HBs, and Anti-HBc to 59 HBsAg-positive pregnant women and identified HBV DNA using nested PCR in their cord blood during delivery for evidence of exposure to HBV DNA. The expression of TLR2 protein in the placenta was performed using immunohistochemistry analysis. Results. Intrauterine exposure to the hepatitis B virus occurred in 69.5% of all pregnant women who were HbsAg positive. TLR2 expression was predominantly identified in syncytiotrophoblast and cytotrophoblast cells with the highest score in mothers aged 20–35 years (75%), multigravida (58.3%), and mothers with term pregnancies (70.8%). Statistical analysis results showed that placental TLR2 expression did not indicate any association with hepatitis B virus DNA identified in cord blood with a p value of 0.730 and an OR of 0.650 (95% CI 0.173–2.440). Conclusion. TLR2 expression is not associated with intrauterine exposure of hepatitis B virus.